Forging Industrial Policy: The United States, Britain, and France in the Railway Age (translated by Yekaterina Golovlyanitsina) - Frank R. Dobbin (Journal of Economic Sociology, 2012)
In the middle of XIX century, governments in the US, France and Britain formed markedly different, but equally prosperous, industrial policy strategies. To understand the origins of these different policies, this book examines the evolution of public policies governing one of the first modern industries, the railroads. The historical analysis of secondary sources traces the evolution of both national industrial policy and political cultures in each country. Dobbin shows that governing principles in industrial policies reflect collective meanings from political sphere. Consequently, promotion patterns of industry formation correspond with the development of political institutions. Thus, the differences in the conceptions of economic efficiency could be explained in the terms of different political organization. In addition, the author argues that emerging industrial institutions reproduce those existing ones. Institutional isomorphism is based on shared meanings in political structures, which shape industrial policy defining which policy solutions were perceived as rational, efficient and moral. Dobbin’s theory is a bold approach to developing a full cultural theory. The author challenges conventional thinking in economics, political science, and sociology by arguing that cultural meaning plays an important role in the development of purportedly rational policies designed to promote industrial growth. The journal publishes Russian translation of chapter 1 “Political Culture and Industrial Rationality”? of “Forging Industrial Policy — Political Culture and Industrial Rationality”, in which Frank Dobbin proposes conceptual discussion on the origins of the cross-country differences in industrial policies. To understand the origins of these different policies, the author examines the evolution of public policies governing one of the first modern industries, the railroads.